Addiction and Its Impact among Adolescents’ Health during Covid-19: A Systematic Review - Dipa Ghosh (Indonesian Journal of Global Health Research, 2021)
The COVID-19 pandemic is a considerable burden for countries which hinder to maintain high quality health services among child and adolescent. According to UNICEF 16% of the world’s population is between 10 to 19 (UNICEF, 2019). The objectives of this systematic review was to examine the addiction and its impact among adolescents’ health during Covid-19. PubMed and Google Scholar databases were searched from 08 September 2021 to 17 September 2021. A systematic literature search was performed in accordance with PRISMA chart and 09 literatures were selected. Out of 09 studies, 05 studies are related to internet addiction (one study for ADHD child and adolescents) and 04 studies are related to substance abuse. The reviewed literatures related to internet addiction revealed that, adolescents suffered from irregular sleep patterns, and increased the risk of ‘addictive’ gamers, neuroticism, impulsivity, depression, anxiety, stress, irritability, concentration problems and a deterioration of ADHD symptoms. The quality of life and social life are also influenced. The reviewed literatures related to substance use revealed that the prevalence of nicotine, smoking, alcohol drinking, cannabis and misuse of prescription drugs were higher among adolescents which leads to mental health problems during this period. These addictions have long term effect on adolescent’s mental, social and physical health. So, we should take care of them and aware the adolescents and their parents regarding various impact of addiction. Government and legislative bodies must take action towards the use substances and accessibility of prescribed drugs.